1989
DOI: 10.1128/mcb.9.4.1691
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-responsive elements in the 5' region of the mouse tissue plasminogen activator gene confer two-stage regulation by retinoic acid and cyclic AMP in teratocarcinoma cells.

Abstract: F9 cells induced to differentiate with retinoic acid (RA) increase transcription of the tissue plasminogen activator (t-PA) gene. Further treatment of these cells with cyclic AMP (cAMP) results in an additional stimulation of t-PA gene transcription. To investigate the mechanism of this two-stage regulation, 4 kilobase pairs (kbp) of 5'-flanking sequence from the murine t-PA gene was isolated. Two major start sites for transcription were found, neither of which depended on a classical TATA motif for correct in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 65 publications
4
51
0
Order By: Relevance
“…Finally, it is noteworthy that genes such as c-jun (87), FGF-3 (103), tissue plasminogen activator (104), and the TGF-␤ type II receptor (105) also contain CRE sites and turn on with RA-induced differentiation of EC cells. Like TGF-␤2, their promoters contain additional cis-regulatory elements that provide specificity and ensure that the correct gene is activated at the precise time.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is noteworthy that genes such as c-jun (87), FGF-3 (103), tissue plasminogen activator (104), and the TGF-␤ type II receptor (105) also contain CRE sites and turn on with RA-induced differentiation of EC cells. Like TGF-␤2, their promoters contain additional cis-regulatory elements that provide specificity and ensure that the correct gene is activated at the precise time.…”
Section: Discussionmentioning
confidence: 99%
“…ment of F9 Cells-To determine the temporal relationship between induction of the ␣1,3GT compared by RA to other known markers and to assess the efficiency of differentiation of F9 cells in response to 10 Ϫ7 M RA in our system, we determined the amount of laminin secreted into the cell culture media. It has been shown that the steady-state levels of mRNAs for laminin B1 and B2 increase dramatically following differentiation of F9 cells, and laminin has been defined as a differentiation marker, along with other basement membrane components, such as type IV collagen (␣1) (39,(55)(56)(57)(58)(59)(60). Laminin was detected by an enzyme-linked immunosorbent assay using cell culture media immobilized in microtiter wells and anti-laminin antibody as the detecting reagent.…”
Section: Time Course Of Induction Of ␣13gt Enzyme Activity In F9 Celmentioning
confidence: 99%
“…This postmitotic somatic cell, which is in intimate contact with developing germ cells in seminiferous tubules in the testis, is crucial for all phases of male gametogenesis, including germ cell proliferation, meiosis, and differentiation (15). Genes necessary for the Sertoli cell to support male gametogenesis have been identified, and some progress has been made in identifying regulatory mechanisms that control the transcription of some of these genes, including follicle-stimulating hormone receptor (Fshr), cathepsin L, the inhibin-␤ B subunit, transferrin, Mullerian inhibitory substance, androgen-binding protein, Dnmrt 1, GATA1, GATA4, and tissue plasminogen activator (12,13,15,17,18,21,35,41,43,53). Regulatory regions and specific cis elements that participate in the transcriptional regulation of these genes have been identified in primary Sertoli cells and Sertoli cell lines.…”
mentioning
confidence: 99%